Economic security requires monetary and price stability: analysis of Malaysian macroeconomic and credit data - Abdullah, Adam (ISTAC, 2015)
Money is the common denominator for all economic transactions and monetary economics provides a framework of analysis of the functions of money to measure their effects on monetary and economic systems. The problem for Malaysia is that the ringgit exchanged for RM110/oz of gold in 1970, however, the price of gold has increased to about RM4,700/oz. Accordingly, the value of one ringgit in 1970 has fallen to 2.3 cents in 2015 (=110/4,700), which represents a catastrophic collapse in the store of value function of money, during the 45-year period of the fiat standard. This paper seeks to investigate the affect of monetary theory and banking practice on the Malaysian economy through a full population analysis of money supply, GDP, interest rates and prices. The findings reveal that conventional monetary theories and policies have ensured monetary and financial instability. This research demonstrates that a decline in the value of fiat money, due to an excessive supply of money as a result of aggregate deposit and loan interest, in relation to demand, the effect of which is an exponential increase prices over the long term. The social implication reveals that usury (riba) requires an economy to lower its standard of living through higher prices, to pay for interest (riba), so that wealth is confiscated through an exponential increase in inflation and transferred to the profit and loss statement of the fractional reserve banking system. The solution is to redefine money, not as a commodity, but as an instrument of transfer and apply an Islamic monetary theory of value to the medium of exchange, so that prices remain low and stable over the long term: economic security and sustainability requires monetary and price stability.